The economics of promoting security of energy supply - Machiel Mulder; Arie ten Cate; Gijsbert Zwart (EIB Papers, 2007)
This paper analyses the welfare effects of two policies directed at the security of energy supply: investments in strategic petroleum reserves and a cap on the production of gas from the largest Dutch gas field. Market failures can justify such policies, in particular failure of individual consumers to account for their impact on energy prices and import dependency and, hence, the vulnerability of a country to geopolitical conflicts. But as the costs of investing in strategic reserves and capping gas production are not negligible, these options are welfare enhancing only in specific circumstances. Generally, measures to improve the functioning of energy markets promise to achieve more than investment-intensive measures or those restricting options of profit-maximising agents. However, policy makers might find it politically expedient to adopt rather than reject inefficient security-of-supply policies.
Keywords: 330; Energieversorgung; Energiepolitik; Marktversagen; Wohlfahrtseffekt